Growth and potential of lomatia hirsuta forests from stump shoots in the valley of El Manso/Patagonia/Argentina - Kühn, Hendrik (2021)
Lomatia hirsuta (Lam.) Diels is a pioneer tree species that develops after wildfires, and in advanced successional stages, it is often found as a secondary species in Patagonian forests. However, in El Manso Valley, Province of Río Negro in Western Argentina, L. hirsuta forms mature pure stands, originated from stump shoots. The wood is very attractive for its colourful appearance and beautiful grain. Nevertheless, these forests are not managed for timber production, they are mostly strong thinned for grazing, and the wood is mainly used as firewood. The objective of this study was to evaluate the possibility to improve quality wood production in stands through silvicultural interventions in a sustainable way. Samples have been carried out in stands of different developmental stages. We evaluated the state and quality of the trees, and their growth has been studied by means of trunk analysis. The results indicate that there is significant potential to improve the production of quality wood in dense stands by thinning to release crop trees. Thinning should start in young stands. It also became apparent that forest management is first necessary to stabilise these nearly unattended forests.